Estimativa da lâmina de evaporação no reservatório Armando Ribeiro Gonçálves utilizando diferentes metodologias - Santos, Liherberton Ferreira dos (Universidade Federal Rural do Semi-Árido, 2019)
The knowledge of evaporation in water reservoirs allows the possibility of planning its multiple uses, and therefore of decision making in the implementation of rational water use policies. In the Brazilian semiarid the evaporation process is intense due to its climatic conditions. This paper aims to compare the behaviors of the evaporation estimation models proposed by Linacre (1977), Linacre (1993), Thornthwaite (1948), Kholer et al. (1955), Hargreaves e Samani (1985) and Priestley-Taylor (1972) with the behavior of the Penman (1948), chosen as standard, to recommend the model that most closely approximates it and relies on fewer weather variables; as well as estimate the evaporation in the reservoir Engenheiro Armando Ribeiro Gonçalves, using climatological data from INMET automatic weather station in Mossoró, historical series from 2008 to 2018. In the evaporation estimate, all models underestimated the model by Penman (1948) in annual and monthly analysis, being those that most closely approximated the Priestley-Taylor (1972) and Linacre (1977) models. In monthly analysis, the model of Linacre (1993), was the one that came closest to the standard model, having the lowest number of variables. The average equivalent vessel resulting from evaporation in the Eng. Armando Ribeiro Gonçalves reservoir was 8.89 m3s-1, based on the evaporation estimated by the Penman model (1948)). The Linacre (1977) model can be recommended for annual evaporation estimates and the Linacre (1993) may be recommended for seasonal estimates for water resource management in semiarid regions.
Monografia
Keywords: Evaporação; Condições Climáticas; Modelos de Estimativa; Planejamento; Evaporation; Climatic Conditions; Estimation Models; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA